2018
DOI: 10.1371/journal.pone.0190747
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Perceived Stigmatization Questionnaire for Brazilian adult burn patients

Abstract: Currently, there is no questionnaire to assess perceived stigmatization among people with visible differences in Brazil. The Perceived Stigmatization Questionnaire (PSQ), developed in the United States, is a valid instrument to assess the perception of stigmatizing behaviours among burn survivors. The objective of this cross-sectional and multicentre study was to assess the factor structure, reliability and validity of the Brazilian Portuguese version of the PSQ in burn patients. A Brazilian version of the 21-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…According to the sample size estimation method of the Kendan's sample estimation method of the multifactor analysis, the sample size should be 5 to 10 times of the maximum item number in the questionnaire. [ 21 ] The maximum item number in the questionnaire herein in this study was 52, considering the sample loss rate of 20%, the sample size were 312 to 624 cases. Taking into account the limitations due to the loss of follow-up, human resources, and sample size, there were finally 530 elderly hypertensive participants herein.…”
Section: Methodsmentioning
confidence: 99%
“…According to the sample size estimation method of the Kendan's sample estimation method of the multifactor analysis, the sample size should be 5 to 10 times of the maximum item number in the questionnaire. [ 21 ] The maximum item number in the questionnaire herein in this study was 52, considering the sample loss rate of 20%, the sample size were 312 to 624 cases. Taking into account the limitations due to the loss of follow-up, human resources, and sample size, there were finally 530 elderly hypertensive participants herein.…”
Section: Methodsmentioning
confidence: 99%
“…A comparative study of the RSES in 53 nations, including 10 LMICs, found broad statistical support with a one-factor model [20]. Other country-focused studies, such as in Brazil, also find high internal consistency [23]. However, the amount of variance accounted for by the single factor was low in some countries, especially in Botswana, the Democratic Republic of Congo (DRC) and Ethiopia, where it fell below 30 percent.…”
Section: Rses In Lmicsmentioning
confidence: 96%
“…Higher scores indicated a greater PS behaviour. 97 The psychometric properties of the PSQ were assessed in various studies. 62,95,98,99 Reliability was considered a pivotal component of psychometric properties.…”
Section: Introductionmentioning
confidence: 99%
“…The total score is computed by adding all the item responses and dividing by the total number of items. Higher scores indicated a greater PS behaviour 97 …”
Section: Introductionmentioning
confidence: 99%